Implementasi Sistem Informasi Manajemen Kepegawaian Pada Dinas Pendidikan Kabupaten Mamuju, Sulawesi Barat - Merianti, Puput; Herlina; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
The implementation of information systems in personnel management has become an important effort for public sector organizations to improve administrative effectiveness and human resource management. This study aims to analyze the implementation of the Personnel Management Information System (SIMPEG) at the Education Office of Mamuju Regency, West Sulawesi. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research informants consist of structural officials, SIMPEG administrators, and system users. The findings indicate that SIMPEG has been implemented in managing personnel data and contributes to improving administrative efficiency, data organization, and accessibility. However, the implementation has not yet been fully optimized. This condition is influenced by variations in human resource capabilities, limitations in technological infrastructure, and the lack of structured training and system socialization. The results suggest that the success of SIMPEG implementation is not solely determined by technical aspects but also by management support and organizational readiness. Therefore, strengthening human resource competencies and improving supporting infrastructure are necessary to ensure more effective and sustainable utilization of SIMPEG.